Exploring Parenting Stress in Young Adulthood with Adverse Childhood Experience (ACE) - hanifah hanifah; Hana Panggabean; Rustono Farady Marta (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Adverse Childhood Experience (ACE) has a significant impact on people’s lives. Few studies have been conducted on young parents with ACE in Indonesia, of which indicated that parenting stress is more common in young parents with ACE.The gap between resources, expectations, and negative mental judgment in response to differences lead to parental stress. The purpose of this research is to explore parenting experiences among young adults with ACE, specifically understanding how they cope with stress. This qualitative study adopted a snowball sampling (Yin, 2016) to identify six participants who are currently a parent with ACE. This research employed a phenomenological qualitative design (Yin, 2016). In-depth interviews are the primary data collection and data was analysed with a thematic analysis. The result indicated that ACE has a significant influence on current parenting stress experiences. Religiosity was found to have an essential role in coping with parenting stress. Cultural standard is a significant characteristic of a nation’s culture, impacting an individual’s thought patterns, emotions, and behavior. Religiosity is an appreciation of a specific religion that helps overcome parenting stress. The ability to overcome this situation, find personal growth, and appreciate life and spiritual changes is called post-traumatic growth.